PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN KUANTUM PADA MOTIVASI BELAJAR MAHASISWA UNTUK MATA KULIAH WRITING MAHASISWA PRODI PENDIDIKAN BAHASA INGGRIS - Wigati, Fikri Asih; Pujiawati, Nia (Majalah Ilmiah SOLUSI, 2012)
Students often face the problem of having low motivation in joining writing class. Therefore the research was aimed to know the effect of Quantum Teaching Strategy ( QTS) on the student’s motivation in comparison to Conventional Teaching Strategy ( CTS). The quantitative research was to measure the effect of QTS on students’ motivation. The data was taken from an experimental research by using questionnaires. the finding showed that QTS affected the performance of English Speaking skill. The teaching strategy questionnaire was also used to get Student’s opinion about teaching method they had gotten to support the validity of the hypothesis. The result shows that the students are motivated to be involved in the learning process.